Development Of Adolescent Sexuality Education E-Module With Autism Spectrum Puberty For Parents - Andajani, Sri Joeda; Sujarwanto; Mardhiyah, Iklil Rif'at Rifdah (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Every teenager experiences changes during adolescence, even those who are autistic. Adolescents on the autism spectrum are more prone to experience sexual harassment because of their weak understanding of sexuality and frequent displays of inappropriate sexual behaviour. Method: The purpose of this project is to develop a product in the form of an e-module for parents on the autistic spectrum about adolescent sexuality education, as well as to explain the viability of the product to material specialists. Only the development step was modified in the research design, which was based on the ADDIE development design from Branch 2010. Procedures for acquiring data entail the creation of data and the use of validation techniques by experts in the media and material. Result: By examining the expert validation instrument score analysis data, one can determine that this product is practicable and of high quality. It is viable to inform parents of teenagers on the autism spectrum, as evidenced by the expert validation test results, which received a percentage score of 87 per cent. The expert validation test results for the content received a percentage score of 84 per cent, indicating that it was appropriate for learning by adolescents on the autistic spectrum. Conclusion: This study concludes that the E-module of Adolescent Sexuality Education with the Autistic Spectrum of Puberty for Parents deserves to be developed.